2013
DOI: 10.1038/mt.2012.234
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived Stromal Cells Overexpressing Vascular Endothelial Growth Factor Accelerate Mouse Excisional Wound Healing

Abstract: Angiogenesis is essential to wound repair, and vascular endothelial growth factor (VEGF) is a potent factor to stimulate angiogenesis. Here, we examine the potential of VEGF-overexpressing adipose-derived stromal cells (ASCs) for accelerating wound healing using nonviral, biodegradable polymeric vectors. Mouse ASCs were transfected with DNA plasmid encoding VEGF or green fluorescent protein (GFP) using biodegradable poly (β-amino) esters (PBAE). Cells transfected using Lipofectamine 2000, a commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 47 publications
(58 reference statements)
2
59
0
1
Order By: Relevance
“…Also, the gene expression profile of the transplanted cells is crucial for their therapeutic effect. [17][18][19] Therefore, next-generation delivery systems should protect bioactive agents in the wound environment, provide sustained release of the bioactive molecules, and adequately modulate the fate, location, and phenotype of transplanted cells.…”
Section: Basic and Experimental Researchmentioning
confidence: 99%
“…Also, the gene expression profile of the transplanted cells is crucial for their therapeutic effect. [17][18][19] Therefore, next-generation delivery systems should protect bioactive agents in the wound environment, provide sustained release of the bioactive molecules, and adequately modulate the fate, location, and phenotype of transplanted cells.…”
Section: Basic and Experimental Researchmentioning
confidence: 99%
“…VEGF and bFGF, however, are decreased in delayed cutaneous wounds, including diabetic wounds and chronic ulcers (17)(18)(19). Inhibition of VEGF and bFGF by neutralizing antibodies results in a decrease in the migration of fibroblasts and a delay in wound healing (20), while treatment with recombinant bFGF and VEGF, or overexpression of VEGF accelerates wound healing (14,21,22). Therefore, it is a potentially clinically beneficial to increase the levels of VEGF and bFGF in cutaneous wounds, particularly in delayed wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] MSCs are multipotent cells that can differentiate along different tissue-specific pathways, including bone cells (osteoblasts), cartilage cells (chondrocytes), and fat cells (adipocytes). 56 Most of these differentiations require directed induction. For example, our previous study demonstrated that without induction for chondrogenic differentiation, MSCs would not differentiate until 4 weeks.…”
Section: Discussionmentioning
confidence: 99%